Vitamin D Status and Severe COVID-19 Disease Outcomes in Hospitalized Patients. (August 2021) - Pecina, Jennifer L.; Merry, Stephen P.; Park, John G.; Thacher, Tom D.
Background: Vitamin D deficiency may increase the risk of severe COVID-19 disease. Objectives: To determine if 25-hydroxyvitamin D [25(OH)D] levels in patients hospitalized for COVID-19 were associated with the clinical outcomes of days on oxygen, duration of hospitalization, ICU admission, need for assisted ventilation, or mortality. Methods: We conducted a retrospective study of 92 patients admitted to the hospital with SARS-CoV-2 infection between April 16, 2020 and October 17, 2020. Multivariable regression was performed to assess the independent relationship of 25(OH)D values on outcomes, adjusting for significant covariates and the hospitalization day the level was tested. Results: About 15 patients (16.3%) had 25(OH)D levels <20 ng/mL. Only 1 patient (3.4%) who had documented vitamin D supplementation prior to admission had 25(OH)D <20 ng/mL. Serum 25(OH)D concentrations were not significantly associated with any of our primary outcomes of days on oxygen, duration of hospitalization, intensive care unit (ICU) admission, need for mechanical ventilation, or mortality in any of the adjusted multivariable models. Adjusting for the hospital day of 25(OH)D sampling did not alter the relationship of 25(OH)D with any outcomes. Conclusion: Vitamin D status was not related to any of the primary outcomes reflecting severity of COVID-19 in hospitalized patients. However, our sample size may have lacked sufficient power to demonstrate a small effect of vitamin D status on these outcomes.